Pembuatan Snack Bar dari Tepung Pisang Kepok (Musa paradisiaca formatypica) dan Pure Pisang Ambon Hijau (Musa paradisiaca sapientum) - George Hutapea; Noviar Harun; Shanti Fitriani (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Snack bar was a solid rod-shaped food, made from a mixture of dry ingredients such as cereals, nuts, grains and fruits which can be consumed as a snack.  Binder is needed in making a snack bar.  Puree can be used as binder in making snack bar.  The snack bar in this research was made from kepok plantain flour and ambon hijau banana puree.  The purpose of this research was to obtain the best ratio of kepok plantain flour and ambon hijau banana puree in making snack bar with the best chemical and sensory characteristics.  This research used a completely randomized design of one factor with four different formulations; kapok plantain flour and ambon hijau banana puree composite in the ratio of 50:50 (TP1), 40:60 (TP2), 30:70 (TP3) and 20:80 (TP4) mixed with other snack bar ingridients. Treatments with 4 replicat, which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%.  The result showed that the ratio of kepok plantain flour and ambon hijau banana puree significantly affected the parameters except fat content and protein content, while sensory assessment had a significantly effected except the parameters of color and density hedonic.  Based on the results, the ratio of kepok banana flour : ambon hijau banana puree (40:60) was chosen as the best formula which had chemical characteristics of 25.55% moisture content, 1.33% ash content, 10.47% fat content, 1.47% protein content, crude fiber content 4.83%, and carbohydrate content of 56.35% and the panelists preferred hedonically with a description of yellowish brown, banana flavored, sweet taste and solid texture.